2018
DOI: 10.1093/biolre/ioy163
|View full text |Cite
|
Sign up to set email alerts
|

Actin cytoskeleton dynamics in mammalian oocyte meiosis†

Abstract: During mitosis, cells undergo symmetrical cell division, while oocyte meiotic maturation undergoes two consecutive, asymmetric divisions that generate a totipotent haploid oocyte and two small polar bodies not involved in DNA replication. This specialized division allows most maternal components be maintained in the oocytes for early embryo development. Nuclear positioning, germinal vesicle breakdown, spindle migration, spindle rotation, chromosome segregation, and polar body extrusion are the most critical ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 120 publications
1
60
0
Order By: Relevance
“…Studies have shown that absence or inhibition of actin filaments leads to abnormal spindle position (Miao et al ). Actin filaments are also essential for cytokinesis, oocyte without actin filaments in the cortex, the cytokinesis rings will not form, and eventually induced failure of the first polar body extrusion (Terada et al ; Duan and Sun ). A fundamental premise to extrude a normal polar body is that the spindle is positioned close to the cortex and actin filaments are normally distributed in the cortex (Kexi and Rong ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that absence or inhibition of actin filaments leads to abnormal spindle position (Miao et al ). Actin filaments are also essential for cytokinesis, oocyte without actin filaments in the cortex, the cytokinesis rings will not form, and eventually induced failure of the first polar body extrusion (Terada et al ; Duan and Sun ). A fundamental premise to extrude a normal polar body is that the spindle is positioned close to the cortex and actin filaments are normally distributed in the cortex (Kexi and Rong ).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian oocytes undergo two consecutive rounds of meiotic division and generate a large haploid egg and two small polar bodies [ 1 ]. The majority of the oocyte cytoplasm is retained during this process, which contains most of the organelles including mitochondria, providing sufficient storage materials and dynamophore (energy carrier) for early embryonic development after fertilization [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3b), and MAPK, PI3K-AKT, HIPPO and calcium signaling pathways (Supp. Figure 4a-d) have been shown previously to play important roles in oocyte structure and function [63][64][65][66][67][68][69] .…”
Section: Follicular Fluid Evs Protein Content and Their Possible Rolementioning
confidence: 76%